Financial Management of the Muhammadiyah Mosque of Bantaeng City, Indonesia as an Improvement Effort Mosque Welfare - A Suarni; S T Wanda; Nurlina Nurlina (Justek : Jurnal Sains dan Teknologi, 2024)
Abstract:  In Indonesia, the mosque is the largest place of worship of the five religions recognized by the people of Indonesia, especially in South Sulawesi. The mosque is one of the most important institutions in Islamic Ummah society and has an important role in daily life. One of the early examples of the Prophet Muhammad when he migrated from Mecca to Medina was building a mosque. Around the mosque there are universities, hospitals, hotels and other facilities that are developing around the mosqueThe research is aimed find out the financial management of the Muhammadiyah Mosque in Bantaeng City Indonesia. The research used qualitative descriptive methods with data collection from observations and interviews. In this study there are 10 Muhammadiyah mosques that are the object of research and the interviews are head of department in mosques and treasures of the mosques. The results of the research found that in the financial reports of the Bantaeng Muhammadiyah Mosque six of them preparing and has financial reports on a regular basis while four of them need to improve transparency in communicating financial information to the Jama’ah. The funds are kept and deposited into the Mosque Account, ensuring efficiency in financial management. Donations from the Jamaah are not only capital for physical development, but also support various religious services and activities. With sustained support, the mosques can continue to improve facilities, services, and support religious activities and education, which in turn strengthen community ties and religious experiences. Indeed, financial management is very important in every mosque because every mosque certainly needs good financial management so that it will make mosque activities easier.